2005
DOI: 10.1180/0026461056940268
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Fe-Ca distributions and related microtextures in syenite alkali feldspar from the Patagonian Andes, Chile

Abstract: Contrasting distribution patterns of Fe and Ca have been found by electron microprobe analysis (EMPA) mapping of alkali feldspar in a quartz syenite from the Patagonian Andes, Chile. They comprise mainly mantle zoning (Fe-rich, Ca-poor rims and Fe-poor, Ca-rich interiors) and corresponding patchy zoning in grain interiors. The rims are dominantly of turbid, patch microperthites associated with abundant micropores, but there remain clear, optically featureless regions almost free of micropores. The interiors ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…This feature has been described by e.g. Gascoyne and Cramer (1987); Abaa (1991); Jenkin et al (1992); Eliasson (1993); Iida et al (1998); Nakano et al (2005); Putnis et al (2007) and Drake et al (2008). They all conclude that the main mineralogical changes in redstained granitic rock are saussuritization and/or sericitization of plagioclase, chloritization of biotite, hematization of magnetite and to a lesser degree sericitization of K-feldspar.…”
Section: Introductionmentioning
confidence: 87%
“…This feature has been described by e.g. Gascoyne and Cramer (1987); Abaa (1991); Jenkin et al (1992); Eliasson (1993); Iida et al (1998); Nakano et al (2005); Putnis et al (2007) and Drake et al (2008). They all conclude that the main mineralogical changes in redstained granitic rock are saussuritization and/or sericitization of plagioclase, chloritization of biotite, hematization of magnetite and to a lesser degree sericitization of K-feldspar.…”
Section: Introductionmentioning
confidence: 87%
“…Further, Černý (1994) summarized that the perthite evolution of pegmatite alkali feldspars takes place by exsolution, coarsening, and recrystallization. Many recent studies on microtextures of alkali feldspars from syenites (Parsons, 1978;Parsons and Brown, 1984;Brown and Parsons, 1994;Nakano et al, 2005;etc. ) and granites Lee and Parsons, 1997;Hashimoto et al, 2005) have shown that patch microperthites are formed along with many micropores by hydrothermal coarsening leading to microscopic turbidity.…”
Section: +mentioning
confidence: 99%
“…The red staining of feldspars, as observed within the damage zones of the Rekvika, Tussøya and Kvaløysletta-Straumsbukta fault zones (Figs 3d and 5f, g), is yet another indication of fault-related fluid infiltration; the red staining may in general be attributed to subsolvus alteration of feldspar minerals through hydrothermal alteration (Boone 1969;Taylor 1977;Smith & Brown 1988;Nakano et al 2005;Drake et al 2008), where plagioclase interacts with fluids to form pseudomorphs after plagioclase occupied by albite and K-feldspar. The red staining itself has been demonstrated to occur as a result of the precipitation of hematite within feldspar pores (Putnis et al 2007).…”
Section: Red Stainingmentioning
confidence: 99%